1990
DOI: 10.1126/science.2374928
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Phospholipase C-γ1 Membrane Association by Epidermal Growth Factor

Abstract: Epidermal growth factor (EGF) treatment of A-431 epidermoid carcinoma cells elicited a redistribution of phospholipase C-gamma 1 (PLC-gamma 1) from a predominantly cytosolic localization to membrane fractions. The temporal coincidence of this redistribution with EGF stimulation of inositol phosphate formation and EGF increased phosphorylation of PLC-gamma 1 suggests that the membrane association of PLC-gamma 1 is a significant event in second messenger transduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
72
1

Year Published

1991
1991
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(74 citation statements)
references
References 25 publications
1
72
1
Order By: Relevance
“…Importantly, growth factor-stimulation not only induces receptor association but also translocation of PLC-γ1 from the cytosol to the membrane (Todderud et al, 1990). Until now, the driving force behind this translocation remains unknown, but it is suspected that the membrane-targeting is linked to growth factor receptors.…”
Section: Activation Of Plc-γ γ γ γ1mentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, growth factor-stimulation not only induces receptor association but also translocation of PLC-γ1 from the cytosol to the membrane (Todderud et al, 1990). Until now, the driving force behind this translocation remains unknown, but it is suspected that the membrane-targeting is linked to growth factor receptors.…”
Section: Activation Of Plc-γ γ γ γ1mentioning
confidence: 99%
“…However, recently, it has been reported that the C-terminal SH2 domain of PLC-γ1 is involved in interactions with synaptojanin (Ahn et al, 1998), the actin-cytoskeleton (Pei et al, 1996), PIP 3 (Bae et al, 1998;Rameh et al, 1998) and FAK (Zhang et al, 1999). These observations suggest that the two SH2 domains of PLC-γ1 are dissimilar and may mediate the recognition of specific phosphorylation sites.Importantly, growth factor-stimulation not only induces receptor association but also translocation of PLC-γ1 from the cytosol to the membrane (Todderud et al, 1990). Until now, the driving force behind this translocation remains unknown, but it is suspected that the membrane-targeting is linked to growth factor receptors.…”
mentioning
confidence: 99%
“…In quiescent cells, cytosolic sequestration of PLC-␥1 limits access to PI(4,5)P 2 in the plasma membrane. Cell stimulation induces membrane recruitment of PLC-␥1 and its tyrosine phosphorylation, essential steps in PLC-␥1 activation (2,23,36). Key components of PLC-␥ that are involved in these activation events are located within a region unique to PLC-␥ between the X and Y portions of the catalytic domain.…”
mentioning
confidence: 99%
“…PLC γ appears to be regulated by tyrosine phosphorylation in response to growth factor receptor occupancy [5]. The phosphorylation of PLC γ does not affect the kinetic properties of the enzyme, but causes a redistribution of the enzyme from the cytosol to cell membrane [6,7]. Tyrosine phosphorylation of PLC γ promotes its association with actin components of the cytoskeleton [8,9].…”
mentioning
confidence: 99%